Safety and Persistence of Non-Animal Stabilized Hyaluronic Acid Fillers for Nasolabial Folds Correction in 30 Indian Patients - Arsiwala, Shehnaz Z (Medknow Publications & Media Pvt Ltd, 2010)
BACKGROUND: Correction of nasolabial creases through minimally invasive procedures is increasingly being sought by patients. Injecting non-animal stabilized hyaluronic acid filler is a highly effective method to achieve an optimal and persistent cosmetic result AIMS: To evaluate the efficacy, persistence and safety of Restylane and Perlane (Q-Med, Sweden) for correction of nasolabial folds in Indian patients MATERIALS AND METHODS: Thirty Indian patients with mild, moderate and severe nasolabial folds (based on Wrinkle Assessment Scale) were recruited in the study after informed consent for correction of their folds with Restylane or Perlane or both. Injections were administered in a single sitting after global assessment of the patient's face using Wrinkle assessment scale (WAS).Optimal filling was performed by using appropriate techniques and its safety and efficacy assessed independently by the investigator as well as by patients at immediately, 3, 6 and 9 months post-procedure. Any adverse reactions were noted. RESULTS: Twenty two females and 8 males (age range 45-55 years, mean age 52 years) were recruited in the study. An optimum cosmetic correction was obtained in all patients. The efficacy increased with time and was greatest at 3 months after the treatment. Grade 2 improvement was maintained at 9 months in mild and moderate folds, and grade 3 improvement for severe folds. Minor post injection side effects like erythema at puncture site, needle marks and bruising were seen. CONCLUSION: Restylane and Perlane are safe and effective dermal fillers for correction of nasolabial creases and offer immediate effect.